2016
DOI: 10.1080/09603409.2016.1171952
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the oxidation of Ni-based superalloys for turbine disc applications: surface condition, applied load and mechanical performance

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 92 publications
2
23
0
Order By: Relevance
“…The alloy contains sufficiently high concentrations of chromium necessary to form a surface layer of chromia and provide the alloy with the required oxidation resistance at operating temperatures. Previous work conducted on this alloy at 1 bar pressure and temperature generally between 700°C and 800°C, has shown that a continuous chromia layer does form on the alloy surface along with sub-surface alumina penetrations [2][3][4][5][6][7]. The rate of chromia growth was shown to be enhanced compared with that formed on chromium or an austenitic steel [8].…”
Section: Introductionmentioning
confidence: 83%
“…The alloy contains sufficiently high concentrations of chromium necessary to form a surface layer of chromia and provide the alloy with the required oxidation resistance at operating temperatures. Previous work conducted on this alloy at 1 bar pressure and temperature generally between 700°C and 800°C, has shown that a continuous chromia layer does form on the alloy surface along with sub-surface alumina penetrations [2][3][4][5][6][7]. The rate of chromia growth was shown to be enhanced compared with that formed on chromium or an austenitic steel [8].…”
Section: Introductionmentioning
confidence: 83%
“…If diffusion of oxygen through a growing oxide scale were the rate determining process for the weight gains, the parabolic rate constant, k p , for Nb 25 Cr 8.3 Si 66.7 at 1000°C can be evaluated to be: k p = 5.8 © 10 ¹8 (mg 2 /cm 4 /s), which is three orders of magnitude smaller than that for some commercial Ni-based superalloys at the same temperature. 18) At 1100°C ( Fig. 10(c)), the Cr 33.3 Si 66.7 alloy exhibited more pronounced weight gains, while the other alloys exhibited small weight change during oxidation up to 500 h. On the contrary, the weight gain of the Cr 33.3 Si 66.7 alloy at 1200°C appears to be lower than that at 1100°C.…”
Section: Oxidation Behaviormentioning
confidence: 92%
“…At this stage in the oxidation process, the ease that oxidising elements diffuse through a growing surface oxide layer becomes a significant factor [10]. Investigations into the steady state oxidation of the nickel-based disc alloy of interest in this paper have been conducted [11][12][13][14][15][16][17] providing data for lifing models to predict, for instance, the onset of breakaway oxidation [18], or the loss of cross-section and mechanical integrity.…”
Section: N Warnken Amentioning
confidence: 99%
“…In a recent experiment [33] intended to examine the effect of elevated air pressure on the oxidation properties of a nickel-based superalloy, high-pressure tests resulted in the formation of a continuous external oxide layer of nickel chromite spinel (NiCr 2 O 4 ) rather than the more usual titanium doped chromia, (Ti, Cr) 2 O 3 , observed at atmospheric-pressure [11][12][13][14][15][16][17]. This result was unexpected and was unlikely to be a result of the difference in test pressure.…”
Section: N Warnken Amentioning
confidence: 99%